2017
DOI: 10.1038/nri.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Translation inhibition and stress granules in the antiviral immune response

Abstract: Efficient viral gene expression is threatened by cellular stress response programmes that rapidly reprioritize the translation machinery in response to varied environmental assaults, including virus infection. This results in inhibition of bulk synthesis of housekeeping proteins and causes the aggregation of messenger ribonucleoprotein complexes into cytoplasmic foci that are known as stress granules, which can entrap viral mRNAs. There is accumulating evidence for the antiviral nature of stress granules, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
331
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(358 citation statements)
references
References 131 publications
12
331
0
1
Order By: Relevance
“…In recent years, SGs have increasingly been seen as important antiviral signaling platforms (2,(4)(5)(6)(7). Several molecules involved in RLR signaling and stress response signaling have been found to localize in SGs (5,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, SGs have increasingly been seen as important antiviral signaling platforms (2,(4)(5)(6)(7). Several molecules involved in RLR signaling and stress response signaling have been found to localize in SGs (5,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…These structures have been identified in plant, yeast, and mammalian cells, and have been characterized microscopically by electron microscopy and immunofluorescence approaches . Stress granules were found to be nonmembranous cytoplasmic structures that usually formed via a multistep process in response to stresses that resulted in translational arrest, such as viral infections, heat, oxidation, and starvation . A recent study has shown that stress granules contain a stable core region surrounded by a dynamic shell‐like structure .…”
Section: The Formation Of Stress Granulesmentioning
confidence: 99%
“…The formation and components of SGs are reviewed in details here [71]. SGs assembly during global translational arrest negatively impact viral genome translation as the SGs reduce the accessibility of translational machinery complexes [72]. Following the relief of translation suppression, the SGs are disassembled via several mechanisms, one of which involves eIF2α dephosphorylation by Growth Arrest and DNA-Damage-inducible 34 (GADD34) protein [73].…”
Section: Zikv Inhibits Cytoplasmic Stress Granules Formationmentioning
confidence: 99%